The Impact of La Nina 2022 on Monthly Rainfall Variabillity in Papua - Kusumaningtyas, Putri Catur; Nugraha, Satria Kirdha; Fauziyah, Nur Aini (University of Muhammadiyah Sumatera Utara, 2025)
ENSO (El Nino Southern Oscillation) is a phenomenon of sea surface temperature (SST) deviation in the Central and Eastern equatorial Pacific Ocean (Nino 3.4). ENSO phase consists of two deviations, namely El Nino and La Nina. La Nina has an impact on increasing rainfall in the Nino 3.4 region. Indonesia, which is part of the Nino 3.4 region, is affected by La Nina in the JJA period (June July August). With research conducted in Eastern Indonesia, Papua in the 2022 La Nina period has varying results. Through four observation points namely Sorong, Enarotali, Jayapura and Merauke. The most affected area of La Nina 2022 is Sorong while for the area affected by ENSO activity during the 11 years of observation (2013-2023) is Merauke with a significance value of 0.000306429; 0.000943892; 5.13748E-05. As for the time most affected by La Nina 2022 and ENSO activity 11 years of observation is in the same month of August with a significance value for the Sorong region of 0.011474481; Enarotali 0.006271735; Jayapura 0.431875715; and Merauke 5.13748E-05.